Studi Literatur: Pengalaman Perawat ICU dalam Memberikan Asuhan Keperawatan Spiritual pada Pasien End of Life Care di Masa Pandemi Covid-19 - Evi Nurjanah; Henny Suzana Mediani; Etika Emaliyawati (Universitas Faletehan, 2022)
Spiritual care is a part of end of life care, which role is to provide a sense of comfort and peace to the patient and ease the grieving process for the family. Nevertheless, COVID-19 pandemic caused many challenges experienced by ICU nurses in the implementation of spiritual care. This study aimed to identify empirical evidences of ICU nurses experience in providing spiritual care to end-of-life care patients during COVID-19 pandemic. It used a literature review method, analyzing articles from 5 reputable databases, namely Pubmed, Proquest, CINAHL, Science Direct, and Google Scholar with the range of publication years between 2020 and 2022. The keywords used were 'pandemic COVID-19', 'critical care nursing’, 'end of life care', 'dying', 'spiritual care', and 'nursing experience'. The articles were selected in stages by PRISMA flow. 2,727 articles were identified and selected based on the duplication and the inclusion criteria until 6 analysis-deserve articles were obtained. The analysis results showed that during COVID-19 pandemic spiritual care was an important domain in end of life care. Spiritual care for end-of-life patients can reduce anxiety and ease the grieving process for the family. The implementation of spiritual care during pandemic era experienced many challenges; thus, an innovative strategy was required to implement it. Health care facilities should provide supports for nurses to carry out spiritual care by increasing their competences through education and training.